2018
DOI: 10.6002/ect.tond-tdtd2017.o4
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We found that sex, education level, social status, and home city of patients had a high impact on quality of life. Thus, it is essential to educate both male and female patients regarding sex/gender and health issues before transplant to increase the recipient's physical and mental health dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…There are gender and sex differences that negatively affect women with KF from the initial diagnosis through access to a substitute renal treatment [ 13 , 14 ], including renal transplant [ 15 ]. Some studies have shown lower QoL among women in HD [ 16 ]. Gender differences in self-care of renal patients have been studied scarcely.…”
Section: Introductionmentioning
confidence: 99%
“…There are gender and sex differences that negatively affect women with KF from the initial diagnosis through access to a substitute renal treatment [ 13 , 14 ], including renal transplant [ 15 ]. Some studies have shown lower QoL among women in HD [ 16 ]. Gender differences in self-care of renal patients have been studied scarcely.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study also allowed to find significant correlations between KDQOL-SF dimensions and sociodemographic variables. Male patients had higher scores in the sleep, social support and social aspects domains, while another investigation showed that men had higher scores in the physical and mental dimensions when compared to women (27) . Despite maintaining equivalent total mental and physical components, they were lower than those of the general population and mortality predictors of chronic kidney patients (19) .…”
Section: Discussionmentioning
confidence: 89%